2010
DOI: 10.1007/s13148-010-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic targets of bioactive dietary components for cancer prevention and therapy

Abstract: The emergent interest in cancer epigenetics stems from the fact that epigenetic modifications are implicated in virtually every step of tumorigenesis. More interestingly, epigenetic changes are reversible heritable changes that are not due to the alteration in DNA sequence but have potential to alter gene expression. Dietary agents consist of many bioactive ingredients which actively regulate various molecular targets involved in tumorigenesis. We present evidence that numerous bioactive dietary components can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
201
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(214 citation statements)
references
References 152 publications
(201 reference statements)
6
201
1
2
Order By: Relevance
“…Interestingly, we found that CuB inhibited the expression of both DNMTs and HDACs in these cells. Previous studies have shown that treatment with either DNMTs inhibitor alone or in combination with HDACs inhibitor altered the expressions of TSGs and TPGs in many cancers (3,21,28,30). In general, promoter regions of the TSGs are hypermethylated causing their silencing in cancer and treatment with DNMTs inhibitor has been shown to reactivate their expression by altering their methylation status (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, we found that CuB inhibited the expression of both DNMTs and HDACs in these cells. Previous studies have shown that treatment with either DNMTs inhibitor alone or in combination with HDACs inhibitor altered the expressions of TSGs and TPGs in many cancers (3,21,28,30). In general, promoter regions of the TSGs are hypermethylated causing their silencing in cancer and treatment with DNMTs inhibitor has been shown to reactivate their expression by altering their methylation status (28).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds possess the capability to reverse the epigenetic alterations. Bioactive natural compounds have been shown to restore the expressions of to tumor suppressor genes (TSG) altered during the course of carcinogenesis (2,3). Therefore, the uses of bioactive natural compounds have been a major focus of interest as therapeutic options against various classes of diseases, including cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the bioactive compounds of plant origin that mediate epigenetic modifications there are agents like genistein (soybean), resveratrol (grapes), curcumin (turmeric), tea catechins (green tea), and sulforaphane (cruciferous vegetables) that have been considered in cancer prevention and therapy (Meeran et al, 2010;Li and Tollefsbol, 2010).…”
Section: Polyphenols and Other Plant Compoundsmentioning
confidence: 99%
“…Other bioactive compounds have been reported to inhibit DNMTs or modify histone acetylation, including lycopene, garcinol, luteolin, butein, apigenin, silymarin, rosmarinic acid, anacardic acid or baicalein (Campion et al, 2010;Meeran et al, 2010;Park et al, 2012). Some of them could have some benefits in the treatment or prevention of metabolic disorders.…”
Section: Polyphenols and Other Plant Compoundsmentioning
confidence: 99%